Fabroque rubber reclaimers a rubber reclaiming plant - Fabro, Villamor L.; Roque, Magtangol S. (Diliman, Quezon City College of Engineering, 1964)
Capacity: 20,000 lbs/day -- Land area: 1.0 hectares -- Fixed capital cost: P6,886,554.00 -- Annual sales at maximum production: P3,500,000.00 -- Operating cost at maximum production: P2,137,172.00 -- Pay-off time: 3.3 years -- Break-even point: 33.7% capacity -- Shut-down point: 14.0% capacity
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Rubber plants; Rubber industry and trade